Respiration and applied tension strategies to reduce vasovagal reactions to blood donation: A randomized controlled trial. Issue 2 (29th November 2018) - Mennitto, Serena; Harrison, Johanna; Ritz, Thomas; Robillard, Pierre; France, Christopher R.; Ditto, Blaine
Abstract : BACKGROUND: Whether produced by breathing too fast or too deeply, hyperventilation is common in stressful situations and may contribute to blood donation–related vasovagal symptoms. The effects of some previously tested interventions for vasovagal symptoms, for example, applied tension (AT), may be related to reduction of hyperventilation. More targeted breathing techniques might be useful. STUDY DESIGN AND METHODS: This was a randomized controlled trial comparing the effects of AT, a slow, shallow "anti‐hyperventilation" breathing technique previously tested in phobic individuals (respiration control [RESP]), the combination of AT and RESP, and no intervention on blood donors participating in university clinics. A total of 547 eligible donors were assigned randomly to one of these four groups. Observational, self‐report, and physiologic measures (primarily via respiratory capnometry) were obtained. RESULTS: Although both RESP and AT had some positive impact on blood donation outcome, the effects of RESP were more numerous, albeit limited primarily to donors who had less general fear of medical procedures. For example, lower‐fear donors assigned to practice RESP had significantly lower Blood Donation Reaction Inventory scores and were significantly less likely to require treatment for symptoms than no‐treatment individuals. In general, RESP led to a significant decrease in respiration rate, though it did not influence end‐tidal CO2, a more precise measure of hyperventilation. CONCLUSION: While the mechanisms remain somewhat unclear and the interventions did not benefit more fearful, higher‐risk donors, respiration control is a promising additional approach to reducing vasovagal symptoms.